Endothelin-1 and Norepinephrine Overflow from Cardiac Sympathetic Nerve Endings in Myocardial Ischemia - Masashi Tawa; Satoshi Yamamoto; Mamoru Ohkita; Yasuo Matsumura (Cardiology Research and Practice)
In protracted myocardial ischemia, sympathetic activation with carrier-mediated excessive norepinephrine (NE) release from its nerve endings due to reversal of NE transporter in an outward direction is a prominent cause of arrhythmias and cardiac dysfunction. Endothelin-1 (ET-1) and its receptors are intimately involved in the regulation of this carrier-mediated NE overflow in protracted myocardial ischemia. The ET-1 system is often complex, sometimes involving opposing actions depending on which receptor subtype is activated, which cells are affected, and whether stimuli are endogenously generated or exogenously applied. Therefore, a detailed understanding of the ET-1 system is important for applying drugs acting on this system in clinical settings for the treatment of ischemic cardiac disease. This article provides a detailed analysis of how the ET-1 system is involved in the regulation of carrier-mediated NE release from sympathetic nerve endings in protracted myocardial ischemia.